COMPARISON OF EPICARDIUM ADIPOSE TISSUE THICKNESS IN TREADMILL TEST POSITIVE AND NEGATIVE PATIENT - SURYADEEP GUPTA; GOVIND KOURETI; YOGENDRA SINGH GOND; MAHENDRA CHOURASIYA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The objectives of this study were as follows: (1) To find out the relationship between the epicardial adipose tissue (EAT) thickness and the treadmill (TMT) test results. (2) To find out the correlation between the EAT thickness and waist circumference and serum low-density lipoprotein-cholesterol. Methods: This study was conducted on 77 patients with complaints of chest pain and came for evaluation to our institution during the study period. All the patients were explained about the study, transthoracic echocardiography, and about EAT as newer cardiovascular risk factors. After obtaining their verbal consent to participate in the study, a voluntary written informed consent was obtained from the patient and/or his/her legally acceptable representative. Results: Majority of the patients were in the age group 41–50 years. Males (54.5%) were more in our study compared to the females. Out of the 77 patients with chest pain, who underwent TMT test, the test was positive in 50.6% patients, negative in 42.9% patients, and inconclusive in 6.5% patients. The comparison of fat pad thickness during the systole was found significantly higher in TMT-positive patients and lowest in the inconclusive patients (p<0.05). Conclusion: There was a significant relationship between the TMT results and the EAT thickness in our study. The thickness of EAT was highest in TMT-positive patients and lowest in the TMT inconclusive test result patients.